A grafted epoxy group modified polyvinyl alcohol nanofiltration membrane and preparation method thereof
By grafting epoxy groups on polyvinyl alcohol and crosslinking with polyamine crosslinking agents, the problem of crosslinking modification of PVA films in the prior art is solved, and a low-cost and environmentally friendly film preparation is achieved, with good stability and high water flux.
Patent Information
- Application Number
- CN202211497793.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-28
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2042-11-28
AI Technical Summary
In the prior art, cross-linking modification of polyvinyl alcohol (PVA) films is required under high temperature or acid catalytic conditions, resulting in high production costs and environmental burden.
The crosslinking of the membrane is achieved by grafting the epoxy groups on the polyvinyl alcohol and crosslinking with a polyamine crosslinking agent to form a two-dimensional network without high temperature or acid catalytic conditions.
This method simplifies the preparation process, reduces costs, and the crosslinked membrane has good stability and high water flux, making it suitable for water treatment applications.
Smart Images

Figure CN115672064B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nanofiltration membranes, and in particular to a grafted epoxy group-modified polyvinyl alcohol nanofiltration membrane and a preparation method thereof. Background Art
[0002] Nanofiltration membrane is a pressure-driven membrane. Generally speaking, the required operating pressure is relatively low, about 0.4-1.0 MPa, and the pore size of nanofiltration membrane is in the nanometer level. Nanofiltration membrane has been gradually commercialized since the 1980s. It requires low energy consumption, large water volume, and has the advantages of safety and environmental protection.
[0003] Usually, nanofiltration membranes are composed of a selective separation layer on the top layer and a support layer with a supporting function. The separation layer should have selective permeability, allowing the solvent to pass through quickly and have a high retention performance for the solute. As for the support layer below, it is required to have high strength and toughness and facilitate the rapid penetration of the solvent. Polysulfone membranes have the characteristics of open pores, hydrophilicity, and moderate thickness. At the same time, they have certain strength and toughness, which can effectively reduce resistance and are suitable for use as the base membrane of nanofiltration membranes.
[0004] In the process of preparing thin-layer composite membranes, the separation layer plays a vital role, so researchers usually focus on the preparation of the separation layer. The materials used to prepare the separation layer of nanofiltration membranes are mainly the following: cellulose acetate, sulfonated polyether sulfone, polyvinyl alcohol and polyamide, among which nanofiltration membranes made of polyvinyl alcohol materials are widely used in the current market.
[0005] Polyvinyl alcohol (PVA) is a hydrolysis product of polyvinyl acetate. Because its main chain is rich in hydroxyl groups, it has good film-forming properties, hydrophilicity and anti-fouling properties. It is an ideal membrane material and is suitable for pressure membranes designed for various water treatment applications. However, the alcohol hydroxyl groups in PVA are very poorly active at room temperature, and the PVA membrane is very easy to swell or even dissolve in water, which limits its large-scale application. Therefore, it is necessary to modify PVA to minimize its swelling and improve its water resistance. The Chinese invention patent with application number CN202210578032.4 discloses "a method for preparing a polyamide nanofiltration membrane with polyaldehyde cross-linked polyvinyl alcohol as an intermediate layer". The data results of this patent can confirm that after cross-linking of polyvinyl alcohol, its own swelling effect can be reduced, making the performance of the nanofiltration membrane product more stable.
[0006] The cross-linking agents used to prepare cross-linked PVA films include glutaraldehyde (GA), glyoxal, etc. in polyaldehydes, citric acid, suberic acid, etc. in polyacids, and can also be boric acid, formic acid, dihydroxymethyl urea, etc. Even GA, which is the easiest to cross-link with PVA in existing research, needs high temperature and acid catalysis to form a tighter cross-linked network. For example, the inventor has invented "a method for preparing a composite nanofiltration membrane with adjustable pore size", which is to prepare a PVA membrane using GA as a cross-linking agent under sulfuric acid catalysis, and its application number is CN202210186781.2. However, the use of high temperature and acid catalysis will increase the production cost of PVA membranes, and there are certain side effects on the environment, which is not conducive to the widespread manufacture and use of PVA membranes. Summary of the invention
[0007] The present invention aims to overcome the defect in the prior art that cross-linking modification of PVA membrane still needs to be achieved under high temperature or acid catalysis conditions, and provides a grafted epoxy group-modified polyvinyl alcohol nanofiltration membrane and a preparation method thereof.
[0008] In order to achieve the above-mentioned invention object, the present invention adopts the following technical scheme:
[0009] A method for preparing a grafted epoxy group-modified polyvinyl alcohol nanofiltration membrane comprises the following steps:
[0010] S1. Preparation of modified polyvinyl alcohol solution: adding a catalyst solution to a polyvinyl alcohol aqueous solution, adjusting the pH of the solution to alkaline, and then adding a solution of a reactant having an epoxy group, so that the polyvinyl alcohol reacts with the solution of the reactant having an epoxy group, thereby grafting the epoxy group onto the polyvinyl alcohol to obtain a modified polyvinyl alcohol solution;
[0011] S2, preparation of a crosslinking agent solution: dissolving a crosslinking agent containing a polyamine structure and a surfactant in an ethanol aqueous solution to obtain a crosslinking agent solution;
[0012] S3, preparation of nanofiltration membrane: spread the crosslinking agent solution in S2 on the polysulfone base membrane, remove the excess solution after standing and dry, then add the modified polyvinyl alcohol solution adjusted to alkaline pH, remove the excess solution after standing, and obtain the modified polyvinyl alcohol nanofiltration membrane after crosslinking and drying.
[0013] The inventors of the present application have changed the previous practice of cross-linking and modifying polyvinyl alcohol under high temperature or acid catalysis conditions, and chose to adopt the method of grafting epoxy groups on polyvinyl alcohol, and using the interaction between the amino groups on the cross-linking agent and the epoxy groups to form a two-dimensional network, so as to achieve the same effect of cross-linking film formation. Among them, the reaction between the amino group and the epoxy group is easy and rapid, and there is no excess product, and it will not inhibit the progress of the reaction. At the same time, because the amino group and the hydroxyl group generated by the reaction are both hydrophilic groups, the water flux of the membrane can still be maintained at a high level after being contaminated, and the water flux attenuation rate before and after contamination can be maintained at a low level. It is an ideal cross-linking reaction for chemically cross-linked membranes.
[0014] The present invention designs and prepares a PVA grafted with epoxy groups, and crosslinks it with a crosslinking agent polyamine (4,4-diaminodiphenyl sulfone, DDS) to form a two-dimensional network. When the modified polyvinyl alcohol nanofiltration membrane grafted with epoxy groups prepared by the above preparation method is subsequently tested for performance, it can be seen from the test results that the water flux of the membrane prepared by the PVA solution after the epoxy groups are grafted is much greater than the water flux of the membrane prepared by the PVA solution, and the epoxy groups in the modified polyvinyl alcohol inhibit the self-crosslinking of PVA and the loose structure formed by the subsequent crosslinking with DDS leads to a significant improvement in the membrane water flux. Overall, the crosslinking effect of the epoxy group and the amino group plays a major role in the membrane performance, and the DDS crosslinking agent plays an auxiliary role in improving.
[0015] In addition, through SEM testing, it was found that the grafted modified polyvinyl alcohol nanofiltration membrane had no obvious voids and defects, and no visible cracks, indicating that it has good uniformity and stability and is suitable for pressure membranes designed for various water treatment applications.
[0016] Preferably, the catalyst solution in S1 is a tetrabutylammonium bromide solution, and the solution of the reactant with epoxy groups is epichlorohydrin; the cross-linking agent containing a polyamine structure in S2 is 4,4-diaminodiphenyl sulfone, and the surfactant is sodium dodecyl sulfonate.
[0017] Preferably, the concentration of the polyvinyl alcohol aqueous solution in S1 is 1-5 g / L, and the concentration of the tetrabutylammonium bromide solution is 5-20 g / L; the concentration of the 4,4-diaminodiphenyl sulfone prepared in S2 is greater than 0 g / L and less than 0.03 g / L, and the concentration of sodium dodecyl sulfate is 0.5-5 g / L.
[0018] Preferably, the volume ratio of the polyvinyl alcohol solution, tetrabutylammonium bromide solution and epichlorohydrin in the modified polyvinyl alcohol solution in S1 is (20-40):2:1.
[0019] Preferably, the ambient temperature when the catalyst solution is added in S1 is 30-65°C.
[0020] The inventors of the present application found during the experiment that too high an ambient temperature when adding tetrabutylammonium bromide catalyst will affect the stability of the modified polyvinyl alcohol solution, causing the solution to produce oil droplet-like precipitation, which will affect the subsequent preparation of the nanofiltration membrane.
[0021] Preferably, the pH range in S1 is 10-12, and the pH range in S3 is 7-9.
[0022] More preferably, the pH value in S1 is 11, and the pH value in S3 is 8.5. The alkali solution used to adjust the pH range in the present invention can be any one of a sodium hydroxide solution and a potassium hydroxide solution, preferably a sodium hydroxide solution. It is worth noting that too high a sodium hydroxide concentration can cause polyvinyl alcohol to self-crosslink and precipitate.
[0023] Acidic conditions conflict with the reaction product HCl, inhibiting the substitution reaction between the hydroxyl groups on the PVA side chains and epichlorohydrin. Secondly, when the solution is alkaline, NaOH can promote the reaction and the progress of the reaction. However, under over-alkaline conditions, the solubility of PVA will decrease accordingly, thereby affecting the absolute number of hydroxyl groups, reducing activity, and causing PVA to precipitate. At a pH of 11, the alkalinity can both promote the reaction and not affect the reaction activity of PVA too much.
[0024] After the pH adjustment in S1 is completed, with the addition of the solvent with epoxy groups, the polyvinyl alcohol and the solution of the reactant with epoxy groups continue to react, and the pH value of the solution changes from alkaline to weakly acidic. Therefore, in the membrane preparation experiment of S3, the pH value of the modified polyvinyl alcohol solution needs to be adjusted to weakly alkaline again.
[0025] Preferably, the solution of the reactant with epoxy groups in S1 is added dropwise, the dropping time is controlled at 30-60 min, and the reaction time of polyvinyl alcohol and the solution of the reactant with epoxy groups is 5-8 h.
[0026] The solvent with epoxy groups is added by dripping, and the dripping time is relatively long, controlled at 0.5-1 h. This is to avoid the solution of the reactant with epoxy groups being added all at once, resulting in insufficient reaction with polyvinyl alcohol. The slow dripping method can increase the contact area between the solution of the reactant with epoxy groups and the polyvinyl alcohol solution, so that each drop of the solution of the reactant with epoxy groups and the polyvinyl alcohol solution can react more fully.
[0027] Preferably, the volume ratio of water to ethanol in the ethanol aqueous solution in S2 is 1:2~3:1.
[0028] Preferably, the drying temperature of the cross-linking agent solution in S3 after standing on the polysulfone membrane is 30-50°C.
[0029] The time for the crosslinking agent solution to stand on the polysulfone membrane should not be too short, as too short a time will result in incomplete crosslinking of the nanofiltration membrane and reduced stability. In the present invention, the preferred standing time is 3 min.
[0030] Preferably, the cross-linking temperature of the modified polyvinyl alcohol solution after adjusting the pH value in S3 after standing is 50-100° C., and the cross-linking time is 5-20 min.
[0031] The standing time of the modified polyvinyl alcohol solution after adjusting the pH value should not be too short, as too short a time will result in incomplete cross-linking of the nanofiltration membrane and weakened stability. In the present invention, the standing time is preferably 5 min.
[0032] A nanofiltration membrane of grafted epoxy group-modified polyvinyl alcohol comprises a polysulfone base membrane and a cross-linked polyvinyl alcohol membrane on its surface, wherein the cross-linked polyvinyl alcohol membrane is obtained by reacting polyvinyl alcohol with epoxy groups and a cross-linking agent with a polyamine structure.
[0033] Therefore, the present invention has the following beneficial effects:
[0034] (1) The present invention forms a two-dimensional network by grafting epoxy groups onto polyvinyl alcohol and cross-linking with a polyamine cross-linking agent, and the cross-linking reaction can occur without high temperature or acid catalysis;
[0035] (2) When the amino groups in the polyamine crosslinking agent are used to react with the epoxy groups for crosslinking, the reaction between the amino groups and the epoxy groups is easy and rapid without any excess products, which is an ideal crosslinking reaction for chemical crosslinking films and does not cause any burden on the environment.
[0036] (3) The preparation process used in the present invention is simple, safe, and low-cost. The prepared modified polyvinyl alcohol nanofiltration membrane has good stability and high flux, and the required reaction conditions are low, which provides a solution for designing a polyvinyl alcohol nanofiltration membrane for ideal commercial applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] The following is a further detailed description of the embodiments of the present invention in conjunction with the accompanying drawings.
[0038] Figure 1 The synthetic route for modified polyvinyl alcohol;
[0039] Figure 2 This is a scanning electron microscope image of the grafted epoxy group-modified polyvinyl alcohol nanofiltration membrane prepared in Example 5. DETAILED DESCRIPTION
[0040] The present invention is further described below in conjunction with specific embodiments. Those of ordinary skill in the art will be able to implement the present invention based on these descriptions. In addition, the embodiments of the present invention involved in the following description are generally only embodiments of a part of the present invention, rather than all embodiments. Therefore, based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work should fall within the scope of protection of the present invention.
[0041]
Modified polyvinyl alcohol solution clarity test
[0042] Example 1
[0043] S1. Preparation of polyvinyl alcohol aqueous solution: Dissolve an appropriate amount of PVA in deionized water, stir in a water bath at 65°C for 120 min to obtain a clear 2 g / L PVA aqueous solution, and then cool at room temperature.
[0044] S2. Preparation of modified polyvinyl alcohol solution: 100 mL of cooled PVA was poured into a four-necked flask, and the three necks of the flask were connected to a mechanical stirring paddle, a thermometer and a constant pressure dropping funnel. After the temperature was controlled at 35°C, 5 mL of 10 g / L tetrabutylammonium bromide (TBAB) solution was added. After TBAB was evenly dispersed in the PVA solution, the pH was adjusted to 11 with a 7.5 g / L sodium hydroxide solution. The constant temperature stirring was continued. After the pH value of the solution was stable, 2.5 mL of epichlorohydrin (ECH) was dripped into the mixed solution drop by drop within 60 min using a constant pressure separating funnel, and the substitution reaction was carried out in the flask for 6 h. The reacted solution was cooled to room temperature and purified with a 50,000 Da ultrafiltration membrane using ultrafiltration membrane technology to obtain a polyvinyl alcohol solution with epoxy groups, which was then stored in a refrigerator at 5°C.
[0045] Example 2
[0046] S1. Preparation of polyvinyl alcohol aqueous solution: Dissolve an appropriate amount of PVA in deionized water, stir in a water bath at 65°C for 120 min to obtain a clear 1 g / L PVA aqueous solution, and then cool at room temperature.
[0047] S2. Preparation of modified polyvinyl alcohol solution: 200 mL of cooled PVA was poured into a four-necked flask, and the three necks of the flask were connected to a mechanical stirring paddle, a thermometer and a constant pressure dropping funnel. After the temperature was controlled at 40°C, 10 mL of 5 g / L TBAB solution was added. After TBAB was evenly dispersed in the PVA solution, the pH was adjusted to 10 with a 7.5 g / L sodium hydroxide solution. The constant temperature stirring was continued. After the pH value of the solution was stable, 5 mL of ECH was dripped into the mixed solution drop by drop within 30 min using a constant pressure separating funnel, and the substitution reaction was carried out in the flask for 8 h. The reacted solution was cooled to room temperature and purified with a 50,000 Da ultrafiltration membrane using ultrafiltration membrane technology to obtain a polyvinyl alcohol solution with epoxy groups, which was then stored in a refrigerator at 5°C.
[0048] Example 3
[0049] S1. Preparation of polyvinyl alcohol aqueous solution: Dissolve an appropriate amount of PVA in deionized water, stir in a water bath at 65°C for 120 min to obtain a clear 5 g / L PVA aqueous solution, and then cool at room temperature.
[0050] S2. Preparation of modified polyvinyl alcohol solution: 40 mL of cooled PVA was poured into a four-necked flask, and the three necks of the flask were connected to a mechanical stirring paddle, a thermometer and a constant pressure dropping funnel. After the temperature was controlled at 50°C, 2.5 mL of 20 g / L TBAB solution was added. After TBAB was evenly dispersed in the PVA solution, the pH was adjusted to 12 with a 7.5 g / L sodium hydroxide solution. The constant temperature stirring was continued. After the pH value of the solution was stable, 1.25 mL of ECH was dripped into the mixed solution drop by drop within 40 min using a constant pressure separatory funnel, and the substitution reaction was carried out in the flask for 5 h. The reacted solution was cooled to room temperature and purified with a 50,000 Da ultrafiltration membrane using ultrafiltration membrane technology to obtain a polyvinyl alcohol solution with epoxy groups, which was then stored in a 5°C refrigerator.
[0051] Test method:
[0052] The solution stability test of Examples 1 to 3 was carried out. The prepared modified polyvinyl alcohol solution was placed in a refrigerator at 5° C. and stored for 3 months. The clarity of the solution was then observed. The test results are shown in Table 1 below.
[0053] Table 1 Effect of reaction temperature on clarity of modified polyvinyl alcohol solution
[0054]
[0055] From the data in the above table, it can be seen that the present invention adjusts the ambient temperature when the TBAB catalyst is added, and performs a solution clarity test under the same conditions. We found that the ambient temperature when TBAB is added has a significant effect on the clarity of the modified polyvinyl alcohol solution. When the temperature exceeds 40°C, an oil droplet-like precipitate will appear in the modified polyvinyl alcohol solution, which is ECH; and when the temperature is controlled at 35°C, the modified polyvinyl alcohol solution can still remain clear. This shows that too high a temperature will lead to excessive reaction, causing the solution to become unstable, causing ECH to precipitate, which is not conducive to the preparation of the subsequent nanofiltration membrane. Therefore, 35°C is preferred for preparing the modified polyvinyl alcohol solution.
[0056] Example 4
[0057] S1. Preparation of polyvinyl alcohol aqueous solution: Dissolve an appropriate amount of PVA in deionized water, stir in a water bath at 65°C for 120 min to obtain a clear 2 g / L PVA aqueous solution, and then cool at room temperature.
[0058] S2. Preparation of modified polyvinyl alcohol solution: 100 mL of cooled PVA was poured into a four-necked flask, and the three necks of the flask were connected to a mechanical stirring paddle, a thermometer and a constant pressure dropping funnel. After the temperature was controlled at 35°C, 5 mL of 10 g / L TBAB solution was added. After TBAB was evenly dispersed in the PVA solution, the pH was adjusted to 11 with a 7.5 g / L sodium hydroxide solution. The constant temperature stirring was continued. After the pH value of the solution was stable, 2.5 mL of ECH was dripped into the mixed solution drop by drop within 60 min using a constant pressure separating funnel, and the substitution reaction was carried out in the flask for 6 h. The reacted solution was cooled to room temperature, and purified with a 50,000 Da ultrafiltration membrane using ultrafiltration membrane technology to obtain a polyvinyl alcohol solution with epoxy groups, which was then stored in a refrigerator at 5°C.
[0059] S3. Preparation of ethanol aqueous solution: water and ethanol are mixed in a volume ratio of 1:2 to obtain ethanol aqueous solution.
[0060] S4. Preparation of crosslinker solution: Dissolve 4,4-diaminodiphenyl sulfone (DDS) and sodium dodecyl sulfonate (SDS) in 100 mL of ethanol-water solution to prepare 0.005 g / L DDS solution and 2 g / L SDS solution for later use.
[0061] S5. Preparation of nanofiltration membrane: Spread the mixed solution of DDS and SDS on the polysulfone base membrane, let it stand for 3 minutes, filter out the excess solution and dry it at 40°C, then pour in the modified polyvinyl alcohol solution with a pH of 7, let it stand for 5 minutes, and place it in an oven at 50°C for cross-linking for 20 minutes to obtain a modified polyvinyl alcohol nanofiltration membrane grafted with epoxy groups.
[0062] Example 5
[0063] S1. Preparation of polyvinyl alcohol aqueous solution: Dissolve an appropriate amount of PVA in deionized water, stir in a water bath at 65°C for 120 min to obtain a clear 2 g / L PVA aqueous solution, and then cool at room temperature.
[0064] S2. Preparation of modified polyvinyl alcohol solution: 100 mL of cooled PVA was poured into a four-necked flask, and the three necks of the flask were connected to a mechanical stirring paddle, a thermometer and a constant pressure dropping funnel. After the temperature was controlled at 35°C, 5 mL of 10 g / L TBAB solution was added. After TBAB was evenly dispersed in the PVA solution, the pH was adjusted to 11 with a 7.5 g / L sodium hydroxide solution. The constant temperature stirring was continued. After the pH value of the solution was stable, 2.5 mL of ECH was dripped into the mixed solution drop by drop within 60 min using a constant pressure separating funnel, and the substitution reaction was carried out in the flask for 6 h. The reacted solution was cooled to room temperature, and purified with a 50,000 Da ultrafiltration membrane using ultrafiltration membrane technology to obtain a polyvinyl alcohol solution with epoxy groups, which was then stored in a refrigerator at 5°C.
[0065] S3. Preparation of ethanol aqueous solution: water and ethanol are mixed in a volume ratio of 1:1 to obtain ethanol aqueous solution.
[0066] S4. Preparation of cross-linking agent solution: Dissolve DDS and SDS in 100 mL of ethanol-water solution in turn to prepare 0.01 g / L DDS solution and 1.5 g / L SDS solution for later use.
[0067] S5. Preparation of nanofiltration membrane: Spread the mixed solution of DDS and SDS on the polysulfone base membrane, let it stand for 3 minutes, filter out the excess solution and dry it at 30°C, then pour in the modified polyvinyl alcohol solution with a pH of 8.5, let it stand for 5 minutes, and place it in an oven at 80°C for cross-linking for 10 minutes to obtain a modified polyvinyl alcohol nanofiltration membrane with grafted epoxy groups.
[0068] Example 6
[0069] S1. Preparation of polyvinyl alcohol aqueous solution: Dissolve an appropriate amount of PVA in deionized water, stir in a water bath at 65°C for 120 min to obtain a clear 2 g / L PVA aqueous solution, and then cool at room temperature.
[0070] S2. Preparation of modified polyvinyl alcohol solution: 100 mL of cooled PVA was poured into a four-necked flask, and the three necks of the flask were connected to a mechanical stirring paddle, a thermometer and a constant pressure dropping funnel. After the temperature was controlled at 35°C, 5 mL of 10 g / L TBAB solution was added. After TBAB was evenly dispersed in the PVA solution, the pH was adjusted to 11 with a 7.5 g / L sodium hydroxide solution. The constant temperature stirring was continued. After the pH value of the solution was stable, 2.5 mL of ECH was dripped into the mixed solution drop by drop within 60 min using a constant pressure separating funnel, and the substitution reaction was carried out in the flask for 6 h. The reacted solution was cooled to room temperature, and purified with a 50,000 Da ultrafiltration membrane using ultrafiltration membrane technology to obtain a polyvinyl alcohol solution with epoxy groups, which was then stored in a refrigerator at 5°C.
[0071] S3. Preparation of ethanol aqueous solution: water and ethanol are mixed in a volume ratio of 3:1 to obtain ethanol aqueous solution.
[0072] S4. Preparation of crosslinker solution: Dissolve DDS and SDS in 100 mL of ethanol-water solution in turn to prepare 0.02 g / L DDS solution and 5 g / L SDS solution for later use.
[0073] S5. Preparation of nanofiltration membrane: Spread the mixed solution of DDS and SDS on the polysulfone base membrane, let it stand for 3 minutes, filter out the excess solution and dry it at 50°C, then pour in the modified polyvinyl alcohol solution with a pH of 9, let it stand for 5 minutes, and place it in an oven at 100°C for cross-linking for 5 minutes to obtain a modified polyvinyl alcohol nanofiltration membrane with grafted epoxy groups.
[0074] Example 7
[0075] S1. Preparation of polyvinyl alcohol aqueous solution: Dissolve an appropriate amount of PVA in deionized water, stir in a water bath at 65°C for 120 min to obtain a clear 2 g / L PVA aqueous solution, and then cool at room temperature.
[0076] S2. Preparation of modified polyvinyl alcohol solution: 100 mL of cooled PVA was poured into a four-necked flask, and the three necks of the flask were connected to a mechanical stirring paddle, a thermometer and a constant pressure dropping funnel. After the temperature was controlled at 35°C, 5 mL of 10 g / L TBAB solution was added. After TBAB was evenly dispersed in the PVA solution, the pH was adjusted to 11 with a 7.5 g / L sodium hydroxide solution. The constant temperature stirring was continued. After the pH value of the solution was stable, 2.5 mL of ECH was dripped into the mixed solution drop by drop within 60 min using a constant pressure separating funnel, and the substitution reaction was carried out in the flask for 6 h. The reacted solution was cooled to room temperature, and purified with a 50,000 Da ultrafiltration membrane using ultrafiltration membrane technology to obtain a polyvinyl alcohol solution with epoxy groups, which was then stored in a refrigerator at 5°C.
[0077] S3. Preparation of ethanol aqueous solution: water and ethanol are mixed in a volume ratio of 1:1 to obtain ethanol aqueous solution.
[0078] S4. Preparation of cross-linking agent solution: Dissolve DDS and SDS in 100 mL of ethanol-water solution in turn to prepare 0.03 g / L DDS solution and 0.5 g / L SDS solution for later use.
[0079] S5. Preparation of nanofiltration membrane: Spread the mixed solution of DDS and SDS on the polysulfone base membrane, let it stand for 3 minutes, filter out the excess solution and dry it at 30°C, then pour in the modified polyvinyl alcohol solution with a pH of 8.5, let it stand for 5 minutes, and place it in an oven at 80°C for cross-linking for 10 minutes to obtain a modified polyvinyl alcohol nanofiltration membrane with grafted epoxy groups.
[0080] Comparative Example 1
[0081] S1. Preparation of polyvinyl alcohol aqueous solution: Dissolve an appropriate amount of PVA in deionized water, stir in a water bath at 65°C for 120 min to obtain a clear 2 g / L PVA aqueous solution, and then cool at room temperature.
[0082] S2. Preparation of modified polyvinyl alcohol solution: 100 mL of cooled PVA was poured into a four-necked flask, and the three necks of the flask were connected to a mechanical stirring paddle, a thermometer and a constant pressure dropping funnel. After the temperature was controlled at 35°C, 5 mL of 10 g / L TBAB solution was added. After TBAB was evenly dispersed in the PVA solution, the pH was adjusted to 11 with a 7.5 g / L sodium hydroxide solution. The constant temperature stirring was continued. After the pH value of the solution was stable, 2.5 mL of ECH was dripped into the mixed solution drop by drop within 60 min using a constant pressure separating funnel, and the substitution reaction was carried out in the flask for 6 h. The reacted solution was cooled to room temperature, and purified with a 50,000 Da ultrafiltration membrane using ultrafiltration membrane technology to obtain a PVA solution with epoxy groups, which was then stored in a 5°C refrigerator.
[0083] S3. Preparation of ethanol aqueous solution: water and ethanol are mixed in a volume ratio of 1:1 to obtain ethanol aqueous solution.
[0084] S4. Preparation of surfactant solution: Dissolve SDS in 100 mL of ethanol-water solution to prepare a 1.5 g / L SDS solution for later use.
[0085] S5. Preparation of nanofiltration membrane: Spread the SDS solution on the polysulfone base membrane, let it stand for 3 minutes, filter out the excess solution and dry it at 30°C, then pour in the modified polyvinyl alcohol solution with a pH of 8.5, let it stand for 5 minutes, and dry it in an oven at 80°C for 10 minutes to obtain a modified polyvinyl alcohol nanofiltration membrane grafted with epoxy groups.
[0086] Comparative Example 2
[0087] S1. Preparation of polyvinyl alcohol aqueous solution: Dissolve an appropriate amount of PVA in deionized water, stir in a water bath at 65°C for 120 min to obtain a clear 2 g / L PVA aqueous solution, and then cool at room temperature.
[0088] S2. Preparation of ethanol aqueous solution: water and ethanol are mixed in a volume ratio of 1:1 to obtain ethanol aqueous solution.
[0089] S3. Preparation of surfactant solution: Add SDS to 100 mL of ethanol-water solution to prepare a 1.5 g / L SDS solution for later use.
[0090] S4. Preparation of nanofiltration membrane: Spread the SDS solution on the polysulfone base membrane, let it stand for 3 minutes, filter out the excess solution and dry it at 30°C, then pour in the PVA aqueous solution, let it stand for 5 minutes, place it in an oven at 80°C for cross-linking for 10 minutes, and obtain the polyvinyl alcohol nanofiltration membrane.
[0091] Performance Testing
[0092] 1. Electron microscopy test
[0093] Depend on Figure 2 It can be seen that the surface of the grafted epoxy group-modified polyvinyl alcohol nanofiltration membrane prepared by the scheme described in Example 5 has no obvious holes and defects, and no visible cracks, indicating that it has good uniformity and stability and is suitable for pressure membranes designed for various water treatment applications.
[0094] 2. Water flux test
[0095] The feed liquid was deionized water with a conductivity of <2 μm / cm, the test pressure was 2 bar, and the test temperature was 25°C.
[0096] The membrane water flux of the grafted epoxy group-modified polyvinyl alcohol nanofiltration membrane prepared in Examples 4 to 7 and the grafted epoxy group-modified polyvinyl alcohol nanofiltration membrane prepared in Comparative Example 1 was tested to explore the effect of the concentration of the crosslinking agent DDS on the membrane water flux. The test results are shown in Table 2 below.
[0097] Table 2 Membrane water flux test at different DDS concentrations
[0098]
[0099] From the data in the above table, it can be seen that the addition of DDS is helpful to improve the water flux of the membrane. As the concentration of DDS increases, the water flux of the corresponding membrane shows a trend of rising and then falling. When the DDS concentration is 0.01 g / L, the water flux is the largest. The reason is that at a lower DDS concentration, the modified polyvinyl alcohol cross-links with the DDS molecules to form a loose network structure, which increases the water flux. As the concentration of DDS increases, the degree of cross-linking increases, resulting in an increase in the network density of the membrane and a decrease in the water flux. Therefore, when the DDS concentration is 0.01 g / L and the PVA concentration is 0.2 g / L (PVA / DDS=25), the membrane water flux is optimal.
[0100] The membrane water flux of the grafted epoxy group-modified polyvinyl alcohol nanofiltration membrane prepared in Example 5, the grafted epoxy group-modified polyvinyl alcohol nanofiltration membrane prepared in Comparative Example 1, and the polyvinyl alcohol nanofiltration membrane obtained in Comparative Example 2 was tested to explore the effect of the epoxy group on the membrane performance. The test results are shown in Table 3 below.
[0101] Table 3 Test of the effect of epoxy groups on membrane properties
[0102]
[0103] From the data in the table above, it can be seen that the water flux of the membrane prepared by the PVA solution after grafting epoxy groups is much greater than that of the membrane prepared by the PVA solution, and the epoxy groups in the modified polyvinyl alcohol inhibit the self-crosslinking of PVA and the loose structure formed by the subsequent crosslinking with DDS leads to a significant improvement in the membrane water flux. Overall, the crosslinking effect of epoxy groups and amino groups plays a major role in the membrane performance, and the DDS crosslinker plays an auxiliary role. The data in this table proves that the crosslinking of epoxy groups and amino groups is a very potential chemical crosslinking reaction in the membrane field.
Claims
1. A method for preparing a polyvinyl alcohol nanofiltration membrane modified by grafted epoxy groups, characterized in that: The following steps are involved: S1. Preparation of modified polyvinyl alcohol solution: adding a catalyst solution to a polyvinyl alcohol aqueous solution, adjusting the pH of the solution to alkaline, and then adding a solution of a reactant having an epoxy group, so that the polyvinyl alcohol reacts with the solution of the reactant having an epoxy group, thereby grafting the epoxy group onto the polyvinyl alcohol to obtain a modified polyvinyl alcohol solution; S2, preparation of a crosslinking agent solution: dissolving a crosslinking agent containing a polyamine structure and a surfactant in an ethanol aqueous solution to obtain a crosslinking agent solution; S3, preparation of nanofiltration membrane: spread the crosslinking agent solution in S2 on the polysulfone base membrane, remove the excess solution after standing and dry, then add the modified polyvinyl alcohol solution adjusted to alkaline pH, remove the excess solution after standing, and obtain the modified polyvinyl alcohol nanofiltration membrane after crosslinking and drying.
2. The method for preparing a grafted epoxy group-modified polyvinyl alcohol nanofiltration membrane according to claim 1, characterized in that: The catalyst solution in S1 is a tetrabutylammonium bromide solution, and the solution of the reactant with epoxy groups is epichlorohydrin; the cross-linking agent containing a polyamine structure in S2 is 4,4-diaminodiphenyl sulfone, and the surfactant is sodium dodecyl sulfonate.
3. The method for preparing a grafted epoxy group-modified polyvinyl alcohol nanofiltration membrane according to claim 2, characterized in that: The concentration of the polyvinyl alcohol aqueous solution in S1 is 1-5 g / L, and the concentration of the tetrabutylammonium bromide solution is 5-20 g / L; the concentration of the 4,4-diaminodiphenyl sulfone prepared in S2 is greater than 0 g / L and less than 0.03 g / L, and the concentration of sodium dodecyl sulfate is 0.5-5 g / L.
4. The method for preparing a grafted epoxy group-modified polyvinyl alcohol nanofiltration membrane according to claim 2, characterized in that: The volume ratio of the polyvinyl alcohol solution, tetrabutylammonium bromide solution and epichlorohydrin in the modified polyvinyl alcohol solution in S1 is (20-40):2:
1.
5. The method for preparing a grafted epoxy group-modified polyvinyl alcohol nanofiltration membrane according to claim 1, characterized in that: The ambient temperature when the catalyst solution is added in S1 is 30-65°C.
6. The method for preparing a grafted epoxy group-modified polyvinyl alcohol nanofiltration membrane according to claim 1, characterized in that: The pH range in S1 was 10-12, and the pH range in S3 was 7-9.
7. The method for preparing a grafted epoxy group-modified polyvinyl alcohol nanofiltration membrane according to claim 1, characterized in that: The solution of the reactant with epoxy groups in S1 is added dropwise, and the dropping time is controlled at 30-60 minutes. The reaction time of polyvinyl alcohol and the solution of the reactant with epoxy groups is 5-8 hours.
8. The method for preparing a grafted epoxy group-modified polyvinyl alcohol nanofiltration membrane according to claim 1, characterized in that: The volume ratio of water to ethanol in the ethanol aqueous solution in S2 is 1:2~3:
1.
9. The method for preparing a grafted epoxy group-modified polyvinyl alcohol nanofiltration membrane according to claim 1, characterized in that: The drying temperature of the crosslinking agent solution described in S3 after standing on the polysulfone membrane is 30-50°C; the crosslinking temperature of the modified polyvinyl alcohol solution after adjusting the pH value described in S3 after standing is 50-100°C, and the crosslinking time is 5-20 min.
10. A nanofiltration membrane of polyvinyl alcohol modified by grafting epoxy groups, characterized in that: The invention comprises a polysulfone base film and a cross-linked polyvinyl alcohol film on the surface thereof. The cross-linked polyvinyl alcohol film is obtained by reacting polyvinyl alcohol with epoxy groups and a cross-linking agent with a polyamine structure.
Citation Information
Patent Citations
Preparation method of composite nanofiltration membrane with adjustable aperture
CN114471162A
Preparation method of polyamide nanofiltration membrane with polyaldehyde cross-linked polyvinyl alcohol as middle layer
CN114870658A
Novel polyvinyl alcohol nanofiltration membrane preparation method
CN106914156A
Reverse demulsifier and preparation method thereof
CN114768309A